Систематична структура урбанофлори Харкова - Звягінцева, К.О. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
В результате проведенного анализа систематической
структуры урбанофлоры Харькова установлен ее видовой
состав, который насчитывает 1092 вида, 511 родов, 116
семейств, 5 классов и 4 отдела. Выявлены особенности
систематической структуры флоры города: высокий ранг
синантропных семейств Polygonaceae и Chenopodiaceae,
повышение ранга семейств Brassicaceae, Fabaceae и
Lamiaceae, пополнение урбанофлоры средиземноморскими
и бореальными видами. Выяснены изменения в
урбанофлоре за 150 лет. Results of an analysis of the systematic (taxonomic) structure of
the Kharkiv urban flora are reported. The species composition is
represented by 1092 species belonging to 511 genera, 116 families,
5 classes, and 4 divisions. Peculiarities of the systematic structure
of the flora were identified: the high ranks of synanthropic families
Polygonaceae, Chenopodiaceae, raising ranks of the families
Brassicaceae, Fabaceae, Lamiaceae, replenishment of the urban
flora by Mediterranean and boreal species. The changes in the
urban flora during the last 150 years are discussed.